1999
DOI: 10.1086/314904
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Neuraminidase Inhibitor Zanamivirin the Treatment of Influenza A and B Virus Infections

Abstract: The efficacy and safety of zanamivir, administered 2x or 4x daily over 5 days, was evaluated in the treatment of influenza infections. A total of 1256 patients entered the study; 57% of those randomized had laboratory-confirmed influenza infection. The primary end point, "alleviation of major symptoms," was created to evaluate differences in clinical impact. In the overall population with or without influenza infection, zanamivir reduced the median number of days to reach this end point by 1 day (P=.012 2x dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(140 citation statements)
references
References 39 publications
2
134
0
4
Order By: Relevance
“…The optimal route of administration and dose of zanamivir in the treatment of naturally acquired in£uenza was explored in a number of studies (Hayden et al 1997;Matsumoto et al 1999;Monto et al 1999a). Their details are summarized in table 1.…”
Section: Clinical Efficacy Studies (A) Experimental In£uenza Infectionmentioning
confidence: 99%
“…The optimal route of administration and dose of zanamivir in the treatment of naturally acquired in£uenza was explored in a number of studies (Hayden et al 1997;Matsumoto et al 1999;Monto et al 1999a). Their details are summarized in table 1.…”
Section: Clinical Efficacy Studies (A) Experimental In£uenza Infectionmentioning
confidence: 99%
“…91,92 The drugs are most effective if administered within the first 30 hours of symptoms in febrile patients and in defined high-risk groups. 93 A recent trial found daily administration of zanamivir for 4 weeks effective in preventing influenza in healthy subjects. Both toxicology 94 and clinical studies 95 have shown this class of compounds to be very safe.…”
Section: Chemoprophylaxis and Pharmacological Treatment Of Influenzamentioning
confidence: 99%
“…Oseltamivir was developed through the modification of the sialic acid analogue framework (Kim et al, 1997). Many reports have shown that both drugs are highly efficient in the treatment of influenza (Cooper et al, 2003;Hayden et al, 1997;Monto et al, 1999;Nicholson et al, 2000). In recent years, peramivir and laninamivir, which also target NA, have been licensed as anti-influenza drugs (Kubo et al, 2010;Yamashita, 2011).…”
Section: Influenza Therapymentioning
confidence: 99%